UNJUK KERJA MODIFIKASI SBR AEROB TERHADAP PENYISIHAN COD - Junaidi, Junaidi (Universitas Diponegoro, 2007)
Sequencing Batch Reactor (SBR) is a modification process from activated sludge that has flexibility in its implementation. In aerobic SBR, all phase is in aerobic cycles those are filling phase, reaction phase, settling phase, drawing phase and idle phase. In this research, idle phase is modified as stabilize phase where biomass is aerated for finite time so sorption capacity of biomass back to normal This research shows that optimum COD removal is achieved in one hour reaction time and stabilization time is 6 which is 97,02 % using active carbon and 95,23 % without active carbon. In conclusion, COD removal capabilities with GAC is better than without GAC.